The first occurrence of machimosaurid crocodylomorphs from the Oxfordian of south-central Poland provides new insights into the distribution of macrophagous teleosauroids - Łukasz Weryński; Błazej Błażejowski; Tomasz Szczygielski; Mark T. Young (PeerJ, 2024)
Teleosauroid thalattosuchians were a clade of semi-aquatic crocodylomorphs that achieved a broad geographic distribution during the Mesozoic. While their fossils are well documented in Western European strata, our understanding of teleosauroids (and thalattosuchians in general) is notably poorer in Central-Eastern Europe, and from Poland in particular. Herein, we redescribe a teleosauroid rostrum (MZ VIII Vr-72) from middle Oxfordian strata of Załęcze Wielkie, in south-central Poland. Until now, the specimen has been largely encased in a block of limestone. After preparation, its rostral and dental morphology could be evaluated, showing the specimen to be a non-machimosaurin machimosaurid, similar in morphology to taxa Neosteneosaurus edwardsi and Proexochokefalos heberti. The well-preserved teeth enable us to study the specimen feeding ecology through the means of comparing its teeth to other teleosauroids through PCoA analysis. Comparisons with inferred closely related taxa suggest that the referred specimen was a macrophagous generalist. Notably, MZ VIII Vr-72 displays a prominent pathological distortion of the anterior rostrum, in the form of lateral bending. The pathology affects the nasal passage and tooth size and position, and is fully healed, indicating that, despite its macrophagous diet, it did not prevent the individual from food acquisition.